Optimizing Natural Deep Eutectic Solvent Citric Acid-Glucose Based Microwave-Assisted Extraction of Total Polyphenols Content from Eleutherine bulbosa (Mill.) Bulb - Bohari Yusuf; Selvi Jumiatul Astati; Mirhansyah Ardana; Herman Herman; Arsyik Ibrahim; Laode Rijai; Firzan Nainu; Islamudin Ahmad (Universitas Gadjah Mada, 2021)
Application of natural deep eutectic solvent (NADES) citric acid-glucose-based microwave-assisted extraction (MAE) method for total polyphenol content (TPC) enriches the use of Eleutherine bulbosa (Mill.) bulb more widely and commercially. Therefore, this study aims to optimize NADES citric acid-glucose-based MAE on the TPC from E. bulbosa bulbs using response surface methodology (RSM). In the present study, the dried sample of E. bulbosa bulb was extracted using the NADES based MAE. Determination of TPC was conducted using Folin-Ciocalteau reagent and standard gallic acid, then measured using a UV-Vis spectrophotometer at 761 nm. Extraction condition optimization of the NADES based MAE method was performed using RSM with Box Behnken Design (four-factors-three-levels and 29 runs) on Design Expert v12. Based on the results study, the optimum condition extraction on the TPC enrichment was obtained at the NADES ratio (citric acid: glucose) 1:1 g/g; solid-liquid ratio 1:8 g/mL; extraction time of 15 min; and 270 Watt microwave power. The confirmation test and scale-up (50 g samples) were obtained with a 61.63 ± 2.23 mg GA/g sample.